A Case of Hemolytic Disease of the Newborn due to Dia Antibody. (22nd November 2015) - Jethava, Ashif; Olivares, Esperanza; Shariatmadar, Sherry
Abstract : Anti-Di a is a clinically significant red cell antibody known to cause hemolytic disease of the newborn. Here, we report on a case of mild hemolytic disease of the newborn caused byDi a antibody. The mother had three prior pregnancies with no history of blood transfusion. She delivered a preterm 35-week-old female newborn by cesarean section. The neonate developed anemia and mild icterus on postnatal day five with hemoglobin of 9500 mg/dL and total bilirubin of 10 mg/dL. The direct antiglobulin test on the neonate's red blood cells was positive. The maternal serum and an eluate from the infant RBCs were negative in routine antibody detection tests but were positive using commercially prepared Di(a+) red cells. The neonate was discharged home in stable condition following treatment with erythropoietin and phototherapy. When a newborn has a positive DAT in the absence of major blood group incompatibility or commonly detected RBC antibodies, an antibody to a low frequency antigen such asDi a must be considered. Further immunohematology tests are required to determine presence of the antibody and the clinician must be alerted to closely monitor the infant for signs of anemia and hemolysis.